2020
DOI: 10.1016/j.omtn.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Definition of miRNA Signatures of Nodal Metastasis in LCa: miR-449a Targets Notch Genes and Suppresses Cell Migration and Invasion

Abstract: Laryngeal cancer (LCa), a neoplasm of the head and neck region, is a leading cause of death worldwide. Surgical intervention remains the mainstay of LCa treatment, but a crucial point is represented by the possible nodal involvement. Therefore, it is urgently needed to develop biomarkers and therapeutic tools able to drive treatment approaches for LCa. In this study, we investigated deregulated microRNAs (miRNAs) in tissues from LCa patients with either lymph node metastases (N+) or not (NÀ). miRNA expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 54 publications
(78 reference statements)
1
28
0
Order By: Relevance
“…MiRNA-34c and miRNA-449a are downregulated in a wide range of cancers, including human breast cancer suggesting their function as potential tumor suppressors [ 43 , 44 , 45 , 46 , 47 ]. Notably, the up-regulation of miRNA-34 and miRNA-449 has been demonstrated to regulate oncogenic pathways including cell proliferation, metastases and apoptotic pathways [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…MiRNA-34c and miRNA-449a are downregulated in a wide range of cancers, including human breast cancer suggesting their function as potential tumor suppressors [ 43 , 44 , 45 , 46 , 47 ]. Notably, the up-regulation of miRNA-34 and miRNA-449 has been demonstrated to regulate oncogenic pathways including cell proliferation, metastases and apoptotic pathways [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the beneficial effects of the upregulation of miR-449a in cancer [ 49 , 50 , 63 , 64 , 65 , 66 , 67 ]. Very recently it has been demonstrated that up-regulation of miR-449a suppresses the proliferation as well as the migration and invasion of laryngeal carcinoma cells targeting Notch1 and Notch2 down-regulation and it has been suggested that miR-449a, alone or in combination therapy with Notch inhibitors, could be used as a potential tool to treat metastatic laryngeal carcinoma [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expression of miR-129-5p has been observed in different types of cancers [27][28][29]. There have widely been reported that microRNAs (miRNAs) are strongly associated with the development and lymph node metastasis of LSCC [30,31]. Our results suggested that miR-129-5p might target and suppress OTX1 in LSCC.…”
Section: Discussionmentioning
confidence: 49%
“…Takeuchi et al ( 33 ) recently reported that a number of microRNAs, including miR-9, miR-10b, miR-21 and miR-132 are aberrantly upregulated in LCa, where they can contribute to the aggressiveness of the LCa. In addition, miR-449a upregulation was found to inhibit cell invasion and motility, suppressed cell proliferation and induced the downregulation of Notch1 and Notch2 in the LCa cell line HEP-2( 34 ). At present, there are no valid prognostic factors that can systematically drive the choice of nodal treatment for LCa.…”
Section: Discussionmentioning
confidence: 99%